EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN PROBLEM POSING PADA POKOK BAHASAN PELUANG DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS XI SMK DI KABUPATEN BOYOLALI - Hidayat Bahktiar; Budi Usodo; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed to find out: (1) which one gives better in mathematics learning achievement, learning model of Think Pair Share (TPS) with Problem Posing, Think Pair Share (TPS) or conventional, (2) which one have better in mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient, (3) in each learning model, which one have better mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient, (4) in each student’s level of Adversity Quotient which one gives better in mathematics learning achievement, learning model of TPS with Problem Posing, TPS or conventional. This research was a quasi-experimental research with 3 x 3 factorial design. The population of the research was all students class XI majors group technology, health and agriculture of SMK in Boyolali. The samples were chosen by using stratified cluster random sampling. The instruments that were used to collect the data were the documentation of mathematics achievement, questionnaire of Adversity Quotient and test of mathematics achievement. The technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed as follows: (1) learning model of TPS with Problem Posing provided better learning achievement than model of TPS and conventional, learning model of TPS provided better learning achievement than conventional, (2) the students having climbers and campers had same achievement, and the students having climbers and campers had better  achievement than those having quitters, (3) in each learning model, the students having climbers and campers had the same achievement, and the students having climbers and campers had better achievement than those having quitters, (4) in each Adversity Quotient, learning model of TPS with Problem Posing provided better learning achievement than TPS and conventional, learning model of TPS provided better learning achievement than conventional.Keywords: Think Pair Share (TPS), Problem Posing, and Adversity Quotient (AQ)